EKSPLORASI PERAN GURU DALAM MENGEMBANGKAN KREATIVITAS USIA DINI MELALUI KEGIATAN SENI GERAK DAN TARI DI LINGKUNGAN SEKOLAH - Raya Idul Fitri; Inayatu Safitri; Zuhrona Siregar; Hida Zahra Lubis (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This article aims to conceptually explore the role of teachers in fostering creativity among early childhood learners through movement and dance activities within the context of preschool education. Creativity during early childhood is a vital foundation for balanced cognitive, emotional, and social development. Movement and dance serve as multisensory media that not only encourage children's self-expression but also enrich their imagination, confidence, and social interaction. Using a qualitative approach based on literature review and theoretical analysis, this article examines various perspectives on how teachers contribute to designing, facilitating, and integrating artistic activities into daily learning. The findings suggest that teachers play a crucial role as facilitators of creative learning environments, inspirators of artistic expression, and mediators of cultural values. When implemented consistently and contextually, movement and dance activities have the potential to strengthen character development and divergent thinking in young children. The conceptual findings of this article imply the need to enhance the pedagogical capacities of early childhood educators and advocate for curricular policies that provide greater space for artistic expression in early education. Further empirical studies are recommended to verify the practical relevance of these insights across diverse educational settings.